2022
DOI: 10.20289/zfdergi.970316
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different nitrogen doses and cultivars on some nutritive value of annual ryegrass (Lolium multiflorum var. westerwoldicum) silage

Abstract: Objective: The objective of this study was to determine the effects of different nitrogen doses and cultivars on some nutritive value of annual ryegrass (Lolium multiflorum var. westerwoldicum) silage. Material and Methods: The study was conducted as a field experiment at Ege University, Department of Field Crops during the growing season of 2019-2020. Four annual ryegrass cultivars (Elif, Big Boss, Baquend, and Medoacus) and five nitrogen doses (0, 75, 150, 225, and 300 kg ha-1) were investigated. Some charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…In addition, in this study, the contents of NDF and ADF in the sugarcane tops silage produced from variety C22 were significantly lower than the contents of NDF and ADF in sugarcane tops silage produced from varieties B9 and T11 at all levels of N application tested. Similar results were found in annual ryegrass silage and Italian ryegrass silage at any N application level, and the lowest NDF and ADF contents were found in annual ryegrass silage produced from the Elif variety, while the lowest NDF content was found in Italian ryegrass silage produced from the Devis variety ( Ertekin et al., 2021 ; Assouma and Çelen, 2022 ). A possible reason for this is that the composition and structure of sugarcane cell walls (cellulose, hemicellulose, and lignin) vary among different forage varieties ( Figueiredo et al., 2019 ).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In addition, in this study, the contents of NDF and ADF in the sugarcane tops silage produced from variety C22 were significantly lower than the contents of NDF and ADF in sugarcane tops silage produced from varieties B9 and T11 at all levels of N application tested. Similar results were found in annual ryegrass silage and Italian ryegrass silage at any N application level, and the lowest NDF and ADF contents were found in annual ryegrass silage produced from the Elif variety, while the lowest NDF content was found in Italian ryegrass silage produced from the Devis variety ( Ertekin et al., 2021 ; Assouma and Çelen, 2022 ). A possible reason for this is that the composition and structure of sugarcane cell walls (cellulose, hemicellulose, and lignin) vary among different forage varieties ( Figueiredo et al., 2019 ).…”
Section: Discussionsupporting
confidence: 80%
“…In this study, when the N application rate was 150 or 300 kg/ha, the DM content in the sugarcane tops silage produced from C22 was significantly higher than that of T11. Similarly, after nitrogen application, the different varieties of annual ryegrass and whole-crop maize silage were also affected by the DM content of their silage, and the DM content of the annual ryegrass silage produced from the variety Baquend at N application rates of 225 kg/ha was the highest, while that of the whole-crop maize silage produced by the variety Andante at N application rates of 168 kg/ha was the highest ( Lynch et al., 2013 ; Assouma and Çelen, 2022 ). Studies have shown that the chlorophyll content of sugarcane leaves is closely related to the accumulation of DM, and at N application rates of 150 or 300 kg/ha, the relative chlorophyll content of C22 sugarcane leaves is significantly higher than that of T11 sugarcane leaves ( Zeng et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation